Reformasi Hukum Keluarga Islam Turki (Status Poligami dalam Perspektif Teori Linguistik-Semantik Muhammad Shahrur) - Abu Yazid Adnan Quthny (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2016)
Renewal of Islamic law in the form of family law legislation began in 1917 with the passing of the Ottoman Law of Family Rights by the Government of Turkey. Family law reform in Turkey was a milestone in the history of family law reform in the Islamic world and has a great influence on the development of family law in other countries. Muhammad Shahrur is one of the contemporary Islamic legal thinkers who did the understanding of Islamic law by way of hermeneutics. One popular method is the analysis of linguistic semantics, and application of modern exact sciences. according Shahrur, marriage principles in the Qur’an are monogamous. While the letter an-Nisa ’verse 3 is often used as the basis of legislation of polygamy actually talking about guardianship of orphans. Therefore, according to the terms Shahrur allowed polygamy (1) wife of second, third, and fourth are widows who have children orphaned, and (2) there must be a sense of worry can not do justice to the orphans. As well as engagement in the Turkish Civil Code of 1926 and arranged in chapters 82-87 in The Cyprus Turkish Family Law of 1951 stipulated in Article 4-5. Turkish family law encourages courts to not hold a special agreement before the marriage, that is to say, if there is a cancellation of the wedding, then judged based on state laws (depending on the law, not a specific agreement between the person who is engaged). If the engagement party is already done, and it turns out the marriage covenant void, then the parties considered responsible for the cancellation of any obligation to pay compensation in the form of changing the party who has incurred costs.This study will discuss the history of the Turkish family law reforms and the factors that influence since Ottoman times to become the Republic of Turkey was formed, explains the elements of a Turkish family law reform, and then associate one element of a Turkish family law reforms (polygamy) with analytical thinking Shahrur linguistic semantics.